Students and the e-book dilemma: a case study - Moisil, Ingrid; Horava, Tony (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
Similar to other academic libraries, the University of Ottawa Library makes ebooks available on many different platforms - aggregators such as ebrary or Project Muse, or major academic publishers‟ own platforms such as Science Direct or Cambridge Books Online. The diversity of e-book platforms can users, as they can't take the time to familiarize themselves with the dozen or more platforms available in their field of study. This impacts and limits the use of these platforms.  In November 2014, the Library surveyed its students about their behaviour, preferences and satisfaction with ebooks used for research and learning purposes. This paper presents the results of the survey and examines how the findings relate to the Library's usage statistics for e-books for 2011-2014.